2021
DOI: 10.3389/fonc.2020.586596
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant EGFR-TKI Therapy for EGFR-Mutant NSCLC: A Systematic Review and Pooled Analysis of Five Prospective Clinical Trials

Abstract: PurposeThe role of neoadjuvant epidermal growth factor receptor (EGFR)-tyrosine kinase inhibitor (TKI) targeted therapy for patients with EGFR-mutant non-small cell lung cancer (NSCLC) has not been clarified. A pooled analysis of prospective clinical trials was conducted to evaluate the efficacy and safety of neoadjuvant EGFR-TKI therapy.MethodsThe PubMed, Embase, Web of Science, and Cochrane Library databases, as well as meeting abstracts were searched for prospective clinical trials evaluating the efficacy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 29 publications
1
53
0
2
Order By: Relevance
“…The rate of pathologic complete response (pCR) obtained with neoadjuvant chemotherapy has been only 2%-15% (9,10). Because targeted therapy and immunotherapy have shown excellent therapeutic promise in metastatic lung cancer, several studies have used them as neoadjuvant therapy for earlier-stage lung cancer (11)(12)(13). Unfortunately, phase 3 clinical trials have shown that neoadjuvant targeted therapy did not prolong overall survival: 9.7% of patients achieved major pathologic response (MPR), and no patients achieved pCR, although the progression-free survival benefit of neoadjuvant erlotinib was approximately 10 months longer than survival with neoadjuvant chemotherapy (14).…”
Section: Introductionmentioning
confidence: 99%
“…The rate of pathologic complete response (pCR) obtained with neoadjuvant chemotherapy has been only 2%-15% (9,10). Because targeted therapy and immunotherapy have shown excellent therapeutic promise in metastatic lung cancer, several studies have used them as neoadjuvant therapy for earlier-stage lung cancer (11)(12)(13). Unfortunately, phase 3 clinical trials have shown that neoadjuvant targeted therapy did not prolong overall survival: 9.7% of patients achieved major pathologic response (MPR), and no patients achieved pCR, although the progression-free survival benefit of neoadjuvant erlotinib was approximately 10 months longer than survival with neoadjuvant chemotherapy (14).…”
Section: Introductionmentioning
confidence: 99%
“…The most recent pooled analysis of 124 patients from five prospective clinical trials demonstrated a satisfactory surgical outcomes and good tolerability to use EGFR TKI in the neoadjuvant treatment of resectable NSCLC. 10 However, results in terms of objective response rate (ORR) and survival are inconsistent in many studies. 11 As the locally advanced NSCLCs are highly heterogeneous, a multidisciplinary team (MDT) involving oncologists, surgeons, pulmonologists and radiation oncologists is necessary to ensure a best practice of precision medicine.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review on neoadjuvant EGFR-TKI therapy for EGFR-mutant NSCLC concluded that this provides a feasible treatment modality with satisfactory surgical outcomes and low toxicity [ 49 ]. However, further phase III trials are necessary to confirm these findings.…”
Section: Neoadjuvant Immunotherapymentioning
confidence: 99%